A new electrospun graphene-silk fibroin composite scaffolds for guiding Schwann cells. Issue 18 (12th December 2017) - Zhao, Yahong; Gong, Jiahuan; Niu, Changmei; Wei, Ziwei; Shi, Jiaqi; Li, Guohui; Yang, Yumin; Wang, Hongbo
Abstract: Graphene (Gr) has been made of various forms used for repairing peripheral nerve injury with favorable electroactivity, however, graphene-based scaffolds in peripheral nerve regeneration are still rarely reported due to the difficulty of realizing uniform dispersion of graphene and electroactive materials at nanoscale as well as lacking biocompatibility. In this paper, graphene-silk fibroin (SF) composite nanofiber membranes with different mass ratios were prepared via electrospinning. Microscopic observation revealed that electrospun Gr/SF membranes had a nanofibrous structure. Electrochemical analysis provided electroactivity characterization of the Gr/SF membranes. The physiochemical results showed that the physiochemical properties of electrospun Gr/SF membranes could be changed by varying Gr concentration. Swelling ratio and contact angle measurements confirmed that electrospun Gr/SF membranes possessed large absorption capacity and hydrophilic surface, and the mechanical property was improved with increasing Gr concentration. Additionally, in-vitro cytotoxicity with L929 revealed that all the electrospun Gr/SF membranes are biocompatible. Moreover, the morphology and quantity showed that the membranes supported the survival and growth of the cultured Schwann cells. Collectively, all of the results suggest that the electrospun Gr/SF membranes combine the excellent electrically conductivity and mechanical strength of the graphene with biocompatibility property of silk to mimic the natural neural cell micro-environment for nerve development.